Exploring the links between household time and food choices in Guatemala - Twyman, Jennifer (International Center for Tropical Agriculture, 2018)
Presented by Jennifer Twyman (CIAT), as part of the Annual Gender Scientific Conference hosted by the CGIAR Collaborative Platform for Gender Research, Addis Ababa, 25-27 September 2018.